Estimations of Japanese university learners' English vocabulary sizes using the vocabulary size test - Stuart McLean; Nicholas Hogg; Brandon Kramer (Vocabulary Learning and Instruction, 2014)
Measuring students’ lexica is time-consuming, as one sitting of the Vocabulary Size Test (VST) usually takes 4060 minutes. As a result, teachers would benefit from being able to make reasonable estimates from commonly available information. This paper aims to investigate: (1) What are the mean vocabulary sizes of students at Japanese universities as a whole, and by university department (hensachi)? and (2) Are a university’s department standardized rank scores (hensachi) a useful proxy for English vocabulary size? This study used a cross-sectional design where 3,449 Japanese university students were tested using Nation and Beglar’s VST. The results showed an average score of 3,715.20 word families and that VST scores were significantly higher for students in higher department hensachi programs. This current department hensachi was also found to have a stronger correlation with VST scores than with other covariates when the entire sample was considered. Lastly, there appears to be a lack of consistent knowledge of the most frequent words of English, suggesting that curriculum designers at Japanese universities should focus on teaching high-frequency English words. Although the findings support the use of the VST for comparing receptive written vocabulary knowledge between learners, they perhaps do not support its use in establishing a vocabulary size to decide lexically appropriate materials.